Neonatal screening: 9% of children with filter paper thyroid‐stimulating hormone levels between 5 and 10 μIU/mL have congenital hypothyroidism - Flávia C. Christensen‐Adad; Carolina T. Mendes‐dos‐Santos; Maura M.F. Goto; Letícia E. Sewaybricker; Lília F.R. D'Souza‐Li; Gil Guerra‐Junior; André M. Morcillo; Sofia Helena V. Lemos‐Marini (Brazilian Society of Pediatrics, 2017)
Objectives: To determine the prevalence of congenital hypothyroidism in children with filter paper TSH levels (f‐TSH) between 5 and 10 μUI/mL in the neonatal screening. Methods: This was a retrospective study including children screened from 2003 to 2010, with f‐TSH between 5 and 10 μIU/mL, who were followed‐up during the first two years of life when there was no serum TSH normalization. The diagnosis of congenital hypothyroidism was defined as serum TSH ≥10 μIU/mL and start of levothyroxine treatment up to 2 years of age. Results: Of the 380,741 live births, 3,713 (1.04%) had f‐TSH between 5 and 10 μIU /mL and, of these, 339 (9.13%) had congenital hypothyroidism. Of these, 76.11% of the cases were diagnosed in the first three months of life and 7.96% between 1 and 2 years of age. Conclusion: The study showed that 9.13% of the children with f‐TSH between 5 and 10 μIU/mL developed hypothyroidism and that in approximately one‐quarter of them, the diagnosis was confirmed only after the third month of life. Based on these findings, the authors suggest the use of a 5 μIU/mL cutoff for f‐TSH and long‐term follow‐up of infants whose serum TSH has not normalized to rule out congenital hypothyroidism.